The Drosophila forked gene encodes two major RNAs, which, in gypsy or springer insertion mutants, are partially or completely truncated within the 5'-ltr of the inserted retrotransposon. - Ishimaru, S.; Saigo, K. (Molecular and General Genetics, 1993)
Mutations in the forked (f) gene of Drosophila cause deformation of bristles and hairs. Our molecular analysis showed the f gene to span more than 30 kb, and to encode two major RNAs, 6.0 and 2.5 kb long, both of which are prematurely terminated in gypsy and springer insertion mutants. These truncated RNAs were polyadenylated using putative polyadenylation signals within the 5'-LTR of the inserted retrotransposon. No evidence was found for effects of the retrotransposon insertions on the promoters for transcription of the 6.0 and 2.5 kb RNAs. In f1 and fx, a single gypsy element was found to be inserted at identical sites in the second intron of region encoding the 2.5 kb f RNA and both truncated and wild-type sized RNAs were detected. Recessive mutations at suppressor of forked (su(f)) increased the fraction of wild-type sized RNAs considerably, suggesting that the wild-type su(f) product either stimulates premature termination at the gypsy LTR or inhibits normal splicing. In f36a, a springer element inserted in the third exon of the region encoding the 2.5 kb f RNA completely suppressed the formation of apparently wild-type transcripts.